ANALISIS PENGELOMPOKAN KUNJUNGAN WISATAWAN KE OBJEK WISATA UNGGULAN DI PROVINSI JAMBI BERBASIS DATA MINING: Data Mining;K-Means;Tourist;Jambi. - Kahar, Novhirtamely; Puad, Lailyn; Istuti , Mona (JURNAL AKADEMIKA, 2020)
Tourist visits to Indonesia, especially the province of Jambi can improve the economy of the community in the tourist area Jambi Province is one of the provinces in Indonesia which is one of the tourist destinations for foreign and international tourists to come to Jambi Province. There are 174 leading tourist attractions in Jambi province according to the questionnaire data taken. The purpose of this study is to analyze the application of datamining in classifying the number of tourist visits to Prov. Jambi uses k-means. The source of research data comes from questionnaire data filled out by the people of Jambi Province. The research data used is the number of tourist visitors last year. The data is grouped into 3 clusters namely C2 = high tourist visits, C1 = moderate tourist visits and C0 = low tourist visits. The final centroid value used at C0 = 5, C1 = 35 and C2 = 17. In order to obtain the results of grouping C0 = 116 attractions, C1 = 18 attractions and C2 = 40 attractions. The results of this analysis can be used as a reference for the Jambi Tourism office to find out the leading tourism objects in Jambi Province according to the Jambi Province Community.